2016
DOI: 10.1177/1742271x15627303
|View full text |Cite
|
Sign up to set email alerts
|

The role of contrast-enhanced ultrasound imaging in the follow-up of patients post-endovascular aneurysm repair

Abstract: Endovascular aneurysm repair is a minimally invasive technique for the treatment of abdominal aortic aneurysms. Patients who undergo endovascular aneurysm repair are potentially at risk of developing problems related to the graft such as the development of endoleaks. Endoleaks can cause expansion of the aneurysmal sac, which can potentially lead to rupture. It is for this reason that lifelong surveillance of patients is required to assess the graft and the aneurysmal sac. This article discusses the role of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A number of different imaging modalities may be used for post‐EVAR surveillance, primarily CTA and CDUS. Magnetic resonance imaging (MRI) and digital subtraction angiography (DSA) are rarely used 4,5 . Computed tomography angiography (CTA) and CDUS assess changes in aneurysm sac size and for the presence of endoleaks.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of different imaging modalities may be used for post‐EVAR surveillance, primarily CTA and CDUS. Magnetic resonance imaging (MRI) and digital subtraction angiography (DSA) are rarely used 4,5 . Computed tomography angiography (CTA) and CDUS assess changes in aneurysm sac size and for the presence of endoleaks.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in many studies, it is shown to have a higher sensitivity than CTA 8,9 . CEUS is used at our institution in cases where there is sac expansion with no endoleak seen on CT or CDUS, given its improved sensitivity 4,10 . Of note, in Australia, CEUS is not currently Medicare rebateable for post‐EVAR imaging.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations